Biometry of the mahseer, Tor putitora (Hamilton) collected from Garo Hills, Meghalaya - Gupta, M Das (Indian Journal of Fisheries, 2011)
There is practically no information onthe biology of the mahseers from the North-Eastem India, except that of Dasgupta (1989),on the copper mahseer Acrossocheilus hexagonolepis(McClelland). Hence this studywas conducted.